Models to Predict the Magnetic Properties of Single- and Multiple-Bridged Phosphate Cuii Systems: A Theoretical Dft Insight - Venegas-Yazigi, D; Venegas-Yazigi, D; Muñoz-Becerra, K; Muñoz-Becerra, K; Aravena-Ponce, D; Aravena-Ponce, D; Soto-Donoso, N; Soto-Donoso, N (Royal Society of Chemistry, 2017)
Copper(ii) phosphate bridged compounds have been studied by DFT methods in order to gain a better understanding of the magnetic exchange interactions through 1,1 and 1,3-bridges, which vary with the bonding modes of the ligand. In many cases phosphate is only one among several bridging ligands making it difficult to identify the predominant exchange pathway. This work proposes a graphical analysis, based on the unrestricted corresponding orbitals (UCO), and the derived "magnetic orbitals" to identify the predominant exchange pathway. Models for the 1,1- and 1,3-bridging modes allow establishing the angle or dihedral dependence of the J values. For the 1,1-bridging mode the θ Cu-O-Cu angle was used. For the 1,3-phosphate the correlation was established with a D-P-Oi-Cui dihedral angle (τ) where D is a dummy atom. Using models with different D-P-Oi-Cui dihedral angles a predictive scheme was generated. Eleven copper(ii) phosphate bridged structures were used to validate the proposed model. The study has shown that antiferromagnetic exchange interactions are primarily produced by phosphate bridges due to the possibility of this ligand that always enables a degree of overlap between the magnetic orbitals. © 2017 the Partner Organisations.